Primary students’ conceptions of the Earth: Re-examining a fundamental research hypothesis on mental models - Vaiopoulou, Julie; Papageorgiou, George (Preschool and Primary Education, 2018)
Research on pupils’ conceptions of the earth has proposed certain mental models within the theoretical perspective known as coherent or theory-like knowledge. Alternatively, the fragmented knowledge hypothesis refutes the existence of such models and proposes a different perspective. Although the relevant discussion has not been converged in to a definite answer, recently, the debate between the two theories has been brought up into consideration by the advances in methodology and statistical analysis. In this paper pupils’ conceptions of the earth were analyzed by latent class analyses. Children’s ideas (N=184, grades 1st to 3rd), were investigated using a closed-ended questionnaire, which includes illustrations corresponding to certain mental models. The results showed that pupils’ conceptions of the earth are not characterized by consistency and thus they do not support the existence of coherent mental models. Implications for theory and practice are discussed.